Quality of Cauca coffee (Coffea arabica L.) under different agricultural management practices (2023)
ABSTRACT : This work focuses, within the coffee production chain, on the pre-harvest, and within this, on the agronomic management of crops, specifically on organic, specialty and traditional management. Three aspects were chosen to evaluate each of these management practices: the physicochemical properties of the soil, the content of pesticides and of metabolites. Finally, the object of study was the species Coffea arabica L., cultivated in the department of Cauca, Colombia. To summarize, when contrasting the three agronomic managements it was found that: 1) In the analysis of the soils, many similarities were found in their physicochemical properties due to the proximity of plots to each other, but differences were found in certain variables and a global classification was achieved by the cluster method. However, these differences are not reflected in the quality as seen in the overall score of the cupping analysis. 2) The agronomic management that is done in the plots that were used for the collection of the samples in the field, does not reflect in the pesticide content, being below the MRL. 3) In metabolite analysis there is a proportion of similarities, as is the case of metabolites by HPLC and by infrared, but there are also marked differences, as seen in the measurement of volatile compounds. These differences, which were not decisive for the quality measured in the cup (overall score), they could be introducing differences in the tasting notes.